The Importance of Effective Management in Driving Economic Growth in Developing Countries - sari, Ni Wayan Nadia; Agistha putri, Melvin; Buda Yasa, I Putu; Salman Alfarisi, Mohammad (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
This article discusses the crucial role of effective management in spurring economic growth in developing countries. Good management is the basis for designing, implementing and optimizing economic policies that support the development of key sectors, factors such as operationally efficient human resource management, innovation and stability. proven to be a key driver in achieving sustainable growth through case study analysis and literature review. This article outlines the positive impact of effective management on company productivity and national economic growth. A comparison of successful management practices with less successful cases provides insight into the strategic importance of directed management and adaptive in facing economic challenges. Apart from that, this article highlights the importance of building managerial capacity through education and training. Improving material skills at various levels of the organization can strengthen economic foundations and open up new opportunities for innovation and investment. Based on these findings, this article concludes that effective management is not only the key to company success but also the main factor that can encourage economic growth in developing countries. Therefore, stakeholders from both the public and private sectors need to work together to strengthen managerial capacity and create an environment which supports exclusive and sustainable economic growth